Endpoint Evaluation of Temporary Anchorage Device Placement in Orthodontic Practice - Prof Muralidhar Mupparapu; Prof Krishna Prasad Lingamaneni; Miss Nirel Gidanian; Dr Rebecca Muller; Dr Brooke Talsania (International Dental Journal, 2023)
Aim or Purpose: Short-term mini-implants or temporary anchorage devices (TAD) were used in Orthodontic practice in patients who require skeletal anchorage for tooth movement. The success of TAD anchorage depends on the location and initial stability of placement among other factors. This outcomes assessment seeks to analyze existing evidence to evaluate the efficacy of CBCT as compared to panoramic radiography in the placement of temporary anchorage devices (TADs) in terms of reducing TAD failure rates and improving patient outcomes. Materials and Methods: Existing literature between 2007-2023 was searched via PubMed, Embase, and Google Scholar using MeSH terms and non-MeSH terms. Articles were limited to human studies in english language, and PRISMA statement guidelines were used to eliminate non-relevant studies. The PICOT question asked was, “Is cone beam computed tomography superior to panoramic radiography as a reliable and safe technique for placement of TADs in the maxilla and mandible?” The results of five articles were considered in the analysis. Results: Across the studies included in the analysis, 236 TADs were placed with the use of CBCT, and 256 TADs were placed with 2D radiography. Placement of TADs using panoramic radiography or other forms of 2D imaging had a failure rate of 29.68%; whereas placement of TADs using CBCT resulted in a 14.40% failure rate. Conclusions: Failures were defined as contact with neighboring roots and the effects, TAD displacement upon force application, and deviation from ideal placement. Based on the results, CBCT-guided TADs had less failure rates as compared with those placed using panoramic radiography alone.